Modelling the marginal effects of energy consumption, ICT, industrialization, and urbanization on environmental sustainability in Somalia: dynamic ARDL and KRLS approaches - Abdikafi Hassan Abdi; Abdifatah Mohamed Muhumed (Discover Sustainability)
Abstract As environmental degradation increasingly threatens ecosystems and economies, understanding the factors shaping ecological sustainability is more urgent than ever. Economic development, technological progress, industrial expansion, and urbanization play a crucial role in determining environmental outcomes, particularly in fragile regions. In Somalia’s vulnerable economy, the balance between fostering economic growth and minimizing ecological footprints remains underexplored. This study addresses this gap by analyzing the effects of economic growth, energy consumption, adoption of information and communication technologies (ICT), industrialization, and urbanization on ecological footprints in Somalia using time-series data from 1990 to 2020. Through a dynamic autoregressive distributed lag (ARDL) model, the study captures both short- and long-term impacts, as well as the shocks of the regressors on ecological footprints. The results indicate that while economic growth reduces ecological footprints in the long-run, energy consumption exacerbates environmental degradation. Strikingly, ICT adoption consistently mitigates ecological footprints by improving resource efficiency and optimizing processes. Conversely, industrialization and urbanization impose significant ecological strain. Employing the Kernel-Based Regularized Least Squares (KRLS) method ensures robust estimates by accounting for the heterogeneity of the pointwise marginal effects of the explanatory variables. According to the findings, Somalia should prioritize promoting renewable energy to reduce dependence on fossil fuels, adopt sustainableindustrial practices, enforce comprehensive urban planning focusing on green infrastructure, leverage ICT for resource optimization, and integrate climate change adaptation into economic strategies.